Language Politeness in Elementary School Students Learning Activities - Linda Eka Pradita; Rachmawati, Umi; Farikah; Delfian Widiyanto; Jendriadi; Ipung Hananto (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Politeness in language is an important indicator of the success of character education which must be cultivated in every aspect of life, both at school, in the family and in society. Nowadays, language politeness in the younger generation is starting to decline both in the school and family environment. In fact, elementary school age is the initial phase for building character education both in communication and behavior. The importance of politeness in language as a reflection of a person's character in establishing communication and human social interaction. This encourages the need to conduct research related to the use of speech in building students' character. This research uses a qualitative approach. Participants in this research were teachers and students. Data is collected through listening, recording and noting the results of observations. The research results found two principles of compliance and violation of language politeness. The principle of obedience consists of the maxim of generosity contained in speech about respecting others and speech about generosity. Meanwhile, the utterance of the maxim of sympathy is contained in the speech of an attitude of sympathy. Furthermore, violations or deviations from the principles of politeness were found in several maxims in Indonesian language learning activities. Violations of the principles of language politeness that were found included violations of language politeness, the maxims of consensus and generosity. This is because students are used to using Javanese and Indonesian in communication so that code mixing occurs.